Isostatic oculomotor patterns in trust perception by facial expressions - I.A. Basul; A.A. Demidov; D.A. Diveev (Экспериментальная психология, 2018)
The article presents the results of analysis of the study in perceptual confidence in Russian and Tuvinian ethnic groups. The objective of the analysis were, the “isostatic” fixation patterns that characterize the perception of representatives of different ethnic and racial groups causing and not causing confidence. It is shown that the isostatic patterns of analytical type are significantly more frequent in the observers when, regardless of ethnic or racial type of the sitters, faces that do not inspire confidence are perceived.